Consensus recommendations for standard investigative workup: report of the International Myeloma Workshop Consensus Panel 3 - Dimopoulos, Meletios A.; Kyle, Robert; Fermand, Jean-Paul; Rajkumar, S. Vincent; San Miguel, Jesus; Chanan-Khan, Asher; Ludwig, Heinz; Joshua, Douglas; Mehta, Jayesh; Gertz, Morie; Avet-Loiseau, Hervé; Beksaç, Meral; et al. (Blood, 2011)
A panel of members of the 2009 International Myeloma Workshop developed guidelines for standard investigative workup of patients with suspected multiple myeloma. Both serum and urine should be assessed for monoclonal protein. Measurement of monoclonal protein both by densitometer tracing and/by nephelometric quantitation is recommended, and immunofixation is required for confirmation. The serum-free light chain assay is recommended in all newly diagnosed patients with plasma cell dyscrasias. Bone marrow aspiration and/or biopsy along with demonstration of clonality of plasma cells are necessary. Serum β2-microglobulin, albumin, and lactate dehydrogenase are necessary for prognostic purposes. Standard metaphase cytogenetics and fluorescent in situ hybridization for 17p, t(4;14), and t(14;16) are recommended. The skeletal survey remains the standard method for imaging screening, but magnetic resonance imaging frequently provides valuable diagnostic and prognostic information. Most of these tests are repeated during follow-up or at relapse.